Crystal structure of chicken γS-crystallin reveals lattice contacts with implications for function in the lens and the evolution of the βγ-crystallins - Sagar, Vatsala (Structure, 2017)
Previous attempts to crystallize mammalian γS-crystallin were unsuccessful. Native L16 chicken γS crystallized avidly while the Q16 mutant did not. The x-ray structure for chicken γS at 2.3Å resolution shows the canonical structure of the superfamily plus a well-ordered N-arm aligned with a β-sheet of a neighboring N-domain. L16 is also in a lattice contact, partially shielded from solvent. Unexpectedly, the major lattice contact matches a conserved interface (QR) in the multimeric β-crystallins. QR shows little conservation of residue contacts, except for one between symmetry-related tyrosines, but molecular dipoles for the proteins with QR show striking similarities while other γ-crystallins differ. In γS, QR has few hydrophobic contacts and features a thin layer of tightly bound water. The free energy of QR is slightly repulsive and AUC confirms no dimerization in solution. The lattice contacts suggest how γcrystallins allow close packing without aggregation in the crowded environment of the lens.